Rosa Winkel, Rosa Listen : Homosexuelle uind "Gesundes Volksempfinden" von Auschwitz bis heute - Stümke, Hans-Georg; Finkler, Rudi (Reinbek : Rowohlt Taschenbuch Verlag, 1981)
Fonds Suzan Daniel (FSD)
Duits
Monografie